2023
DOI: 10.3390/coatings13091603
|View full text |Cite
|
Sign up to set email alerts
|

The Behavior of TiAlN and TiAlCrSiN Films in Abrasive and Adhesive Tribological Contacts

Wadim Schulz,
Vitalij Joukov,
Florian Köhn
et al.

Abstract: Chromium and silicon are often introduced to increase the performance of TiAlN hard coatings in dry tribological contacts. The addition of Cr and Si during a high-power impulse magnetron sputtering (HiPIMS) deposition process leads to high-quality TiAlCrSiN films. In this paper, the analysis of friction and wear of these films is conducted by oscillation tribometry under dry conditions with a subsequent mapping of the surface topography. Both abrasion- and adhesion-dominated conditions are realized using diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…The analysis of the structure of CVD and PVD TiAlSiN coatings deposited on cemented carbide tools indicated that both coatings consisted of nanocrystals embedded in amorphous SiN x [23]. Schulz et al [24] deposited wear-resistive TiAlCrSiN coatings on a WC/Co metal substrate. The TiAlCrSiN coating showed a significant reduction in coefficient of friction due to the addition of Cr and Si to the coating which reduces adhesion.…”
Section: Introductionmentioning
confidence: 99%
“…The analysis of the structure of CVD and PVD TiAlSiN coatings deposited on cemented carbide tools indicated that both coatings consisted of nanocrystals embedded in amorphous SiN x [23]. Schulz et al [24] deposited wear-resistive TiAlCrSiN coatings on a WC/Co metal substrate. The TiAlCrSiN coating showed a significant reduction in coefficient of friction due to the addition of Cr and Si to the coating which reduces adhesion.…”
Section: Introductionmentioning
confidence: 99%